+0  
 
0
59
2
avatar

How do I begin this problem? 

 

Guest Aug 25, 2017

Best Answer 

 #1
avatar+26102 
+2

Start by setting: \(u=\sqrt{11-x^2}\\ .\\u-\frac{2}{u}=1\\\)

 

Rearrange:  \(u^2-u-2=0\\.\\(u-2)(u+1)=0\)

 

So u = 2 or u = -1.  However, the original square root must be positive, so only the first value of u is valid.

 

\(\sqrt{11-x^2}=2\\.\\11-x^2 = 4\\.\\x^2=7\\.\\x=\pm \sqrt7 \)

Alan  Aug 25, 2017
Sort: 

2+0 Answers

 #1
avatar+26102 
+2
Best Answer

Start by setting: \(u=\sqrt{11-x^2}\\ .\\u-\frac{2}{u}=1\\\)

 

Rearrange:  \(u^2-u-2=0\\.\\(u-2)(u+1)=0\)

 

So u = 2 or u = -1.  However, the original square root must be positive, so only the first value of u is valid.

 

\(\sqrt{11-x^2}=2\\.\\11-x^2 = 4\\.\\x^2=7\\.\\x=\pm \sqrt7 \)

Alan  Aug 25, 2017
 #2
avatar+7 
0

¿Cómo escribes para publicar tu pregunta? 

RUTH1998  Aug 25, 2017

17 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details